Analysis of the Journalistic Language Characteristics of Hermawan Arifianto on Liputan6.com - Halimatussa'diyah; Firdausi Nuzula; Wahyunengsih (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
Journalistic language is the language of the press used to write news. The characteristics of journalistic language in writing a news story have several parts, namely communicative language, sentence specifications, word savings, clarity of meaning, redundancy, and cliche (Chaer 2010). This study uses a qualitative approach. The method of data collection in this study used the method of observation and document analysis. This study aims to see how the characteristics of the journalistic language in the eight news articles written by Hermawan Arifianto in the Liputan6.com media, with the results of the study there were 65 data findings. The characteristics of the journalistic language in the eight stories written by Hermawan Arifianto in the Liputan6.com media include 1). the communicative language there are 9 data findings, 2). sentence specifications there are 10 data findings, 3). clarity of meaning there are 37 data findings, 4). word saving there are 4 data findings, and lastly 5). redundancy or non-cliche there are 5 data findings. These results indicate that the characteristics of clarity of meaning are the most commonly found, while the characteristics of word saving and redundancy or non-cliche are found the least.